2020
DOI: 10.1002/adfm.202006236
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Circularly Polarized Light‐Sensing Near‐Infrared Organic Phototransistors for Optoelectronic Cryptographic Primitives

Abstract: Chiral photonics has emerged as a key technology for future optoelectronics, such as quantum information and encryption, by making use of photonic waves from enantiomeric structures. An inevitable challenge for realizing such chiral optoelectronics is the development of near-infrared circularly polarized (NIR CP) light-sensing photodetectors that convert optical power and circular polarization direction into distinguishable electrical signals. Herein, a simple and promising strategy for high-performance NIR CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 72 publications
2
59
0
Order By: Relevance
“…20c shows the D* of the vertical phototransistors as a function of the incident irradiance. In the accumulated region, the calculated maximal D* can reach ≈1.2 × 10 13 Jones under an incident intensity of 0.4 μW/cm 2 , which is superior to some of the reported narrow bandgap organic-based NIR photodetectors [38][39][40][41] . When we extended the NIR light to 740 and 940 nm, the PTCDI-C8 nanowires VPTs have also validated excellent NIR light photoresponse, which are similar to the results obtained at 850 nm NIR light, as shown in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 63%
“…20c shows the D* of the vertical phototransistors as a function of the incident irradiance. In the accumulated region, the calculated maximal D* can reach ≈1.2 × 10 13 Jones under an incident intensity of 0.4 μW/cm 2 , which is superior to some of the reported narrow bandgap organic-based NIR photodetectors [38][39][40][41] . When we extended the NIR light to 740 and 940 nm, the PTCDI-C8 nanowires VPTs have also validated excellent NIR light photoresponse, which are similar to the results obtained at 850 nm NIR light, as shown in Supplementary Figs.…”
Section: Resultsmentioning
confidence: 63%
“…The resulting conjugated polymer, poly[{2,5-bis-(2-octyldodecyl)-3,6-bis-(thien-2yl)-pyrrolo [3,4-c]pyrrole-1,4-diyl}-co-{2,2′-(2,1,3-benzothiadiazole)-5,5′-diyl}] (PODTPPD-BT), exhibited strong optical absorptions in the NIR range. Note that the identical polymer has been reported for the OFETs using SiO 2 /Si substrates [41][42][43] but not applied for flexible NIR-OPTRs (the polymer in ref. [43] was initially synthesized in our group (by the first author in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the identical polymer has been reported for the OFETs using SiO 2 /Si substrates [41][42][43] but not applied for flexible NIR-OPTRs (the polymer in ref. [43] was initially synthesized in our group (by the first author in ref. [43]) and being applied for NIR-OPTRs (by the first author in this paper) but its application has been reported slightly earlier than this work).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the predominant left-handed helical organization and the broad wavelength tunability of the photonic bandgap were harnessed for the detection of CPL, as shown in Figure 8B . This sentence has been modified to By introducing a cholesteric liquid crystal network films (CLCN) on the phototransistor based on small-bandgap conjugated polymer poly[{2,5-bis-(2-octyldodecyl)-3,6-bis-(thien-2-yl)pyrrolo[3,4-c]pyrrole-1,4-diyl}-co-{2,2′-(2,1,3-benzothiadiazole)]5,5′-diyl}] (PODTPPD-BT) as a reflector, Han et al Han et al (2020) reported a near-infrared circularly polarized light–sensing photodetector (NIR CPL-OPTR). Due to the ability of the CLC film to distinguish the polarization direction of CP light, the final NIR CPL-OPTR device achieved a dissymmetry factor of 1.9 ( Figure 8C ).…”
Section: Exploration Of Circularly Polarized Light Detectors With Excellent Performancementioning
confidence: 99%